2020
DOI: 10.3390/biom10091318
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Administration of the Acetylcholinesterase Inhibitor, Donepezil, Interferes with Bone Healing and Implant Osseointegration in a Rat Model

Abstract: Donepezil is an acetylcholinesterase inhibitor commonly used to treat mild to moderate Alzheimer’s disease. Its use has been associated with increased bone mass in humans and animals. However, the effect of postoperative administration of donepezil on bone healing remains unknown. Therefore, this study aimed to assess the impact of postoperative injection of donepezil on bone healing, titanium-implant osseointegration, and soft tissue healing. Twenty-two Sprague-Dawley rats were randomly assigned to receive a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 51 publications
4
13
0
Order By: Relevance
“…Furthermore, the comparable healing observed in empty defects raises a concern regarding the suitability of this bone defect model. However, this model was found to be reliable to study the effect of medications on bone healing based on previous studies Al-Hamed et al, 2020). Therefore, to assess the regenerative potential of L-PRP, it is advised to use a larger bone defect instead of the one used in this study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, the comparable healing observed in empty defects raises a concern regarding the suitability of this bone defect model. However, this model was found to be reliable to study the effect of medications on bone healing based on previous studies Al-Hamed et al, 2020). Therefore, to assess the regenerative potential of L-PRP, it is advised to use a larger bone defect instead of the one used in this study.…”
Section: Discussionmentioning
confidence: 96%
“…This model involves minimally invasive surgery and reduces animal suffering. We have already used it in our previous studies with minimal complications (Al‐Hamed et al, 2020; Al‐Hamed et al, 2021). However, in the current study, our rats were euthanized because of bone fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In addition, this was in agreement with our in vivo study, in which we showed that the AChEI, donepezil, did not affect hemostasis and platelet function. 32 Thus AChEI use does not appear to be associated with increased bleeding risk.…”
Section: Discussionmentioning
confidence: 97%
“…In another article by Al-Hamed et al [10], postoperative administration of donepezil on bone healing was studied in the group of Sprague-Dawley rats. After two weeks of donepezil administration, rats were euthanized, and their bones were analyzed by Micro-CT and histology, with the authors concluding that bone defects and implant osseointegration were significantly reduced compared to the saline-treated rats.…”
mentioning
confidence: 99%